A literary and biographical history, or bibliographical dictionary, of the English Catholics from the breach with Rome, in 1534, to the present time - Gillow, Joseph (Burns & Oates, 1885)
v. 1. A-Curr.--v. 2. D-Grad.--v. 3. Grah-Kemb.--v. 4. Keme-Met.--V. 5. Mey-Zoo.